EFEKTIVITAS METODE PERMAINAN EDUKATIF SEBAGAI UPAYA MENGATASI KESULITAN BELAJAR BAHASA ARAB DI KELAS VII-B MTS AS’ADIYAH PUTRI: Metode permainan edukatif Bahasa Aarab - Sulfiani. M Muliadi (Matluba: Jurnal Pendidikan Bahasa dan Budaya Arab, 2024)
This study uses a quantitative research type with an experimental method that aims to: 1) Determine the educational game method in overcoming difficulties in learning Arabic in class VII-B MTS As'Adiyah Putri, Sengkang center. 2) Determine the effectiveness of the educational game method to overcome difficulties in learning Arabic in class VII-B MTS As'Adiyah Putri, Sengkang center. The population in this study were students of class VII-B MTs As'Adiyah Putri, Sengkang center with samples taken non-randomly which determined special characteristics according to the research objectives of 26 students in one class through two variables, namely variable X in the form of educational game methods and variable Y in the form of student learning outcomes. This study shows that, 1. The analysis carried out by the researcher can be seen that the initial ability of students in learning obtained from the pre-test is in the very low category, namely 44.34 and the post-test is in the very high category, namely 84.38. 2. After conducting learning for 2 meetings by implementing 3 educational game methods, namely chain stories, guessing pictures, and qumi qumi, it can be seen that the students' abilities have increased and they no longer have difficulties in learning Arabic.